2013
DOI: 10.1111/j.1365-3164.2012.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal structure created by canine hair follicle keratinocytes enriched with bulge cells in a three‐dimensional skin equivalent model in vitro: implications for regenerative therapy of canine epidermis

Abstract: Background-Keratinocytes in the hair follicle bulge region have a high proliferative capacity, with characteristics of epithelial stem cells. This cell population might thus be an ideal source for generating the interfollicular epi-dermis in a canine skin equivalent. Hypothesis ⁄ Objectives-This study was designed to determine the ability of canine hair follicle bulge cell-enriched keratinocytes to construct canine living skin equivalents with interfollicular epidermis in vitro. Animals-Four healthy beagle dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The epidermis of the canine nasal planum is on average more than twice the thickness of haired skin in healthy dogs and displays an orthokeratotic SC but focal parakeratosis can occur [14]. One study showed that the healthy canine nasal planum displays a similar pattern of the differentiation markers K14 and K10, desmogleins 1 and 3, and filaggrin, compared to a canine in vitro three-dimensional skin equivalent [15]. Another study reported on comparable mRNA and protein expression of K5 and K10, filaggrin and involucrin in various haired body regions of dogs [16].…”
Section: Introductionmentioning
confidence: 99%
“…The epidermis of the canine nasal planum is on average more than twice the thickness of haired skin in healthy dogs and displays an orthokeratotic SC but focal parakeratosis can occur [14]. One study showed that the healthy canine nasal planum displays a similar pattern of the differentiation markers K14 and K10, desmogleins 1 and 3, and filaggrin, compared to a canine in vitro three-dimensional skin equivalent [15]. Another study reported on comparable mRNA and protein expression of K5 and K10, filaggrin and involucrin in various haired body regions of dogs [16].…”
Section: Introductionmentioning
confidence: 99%
“…94,99 This protrusion is not seen in domestic animals nor in humans, but the term bulge has been used in several publications and refers to the isthmus region. 46,47 In dogs, different SC populations have been identified along the entire isthmus. 25 Like in the dog, the SC bearing regions in the human HF are not yet well defined.…”
Section: Hair Follicle Scsmentioning
confidence: 99%
“…Kobayashi et al dissected and cultured the bulge area of canine hair follicles in vitro and obtained highly proliferative keratinocytes, which shared the same marker expression with mouse and human HFSCs [ 17 , 18 ]. In vitro , these canine HFSCs formed an IFE structure comprising cell layers that expressed markers similar to the normal epidermis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%